Phytochemicals as a potential inhibitor of Spike Protein of SARS-CoV-2 Omicron Variant - Tuti Ratnasari; Faizah Fulyani; Endang Mahati (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: More than 50 mutations have been found in Omicron SARS-CoV-2. Most Omicron mutations are located in the spike protein, which plays a pivotal role in virus infection. The mutated spike protein in the Omicron variant increases virus transmissibility and potentially threatens the effectiveness of COVID-19 vaccines and antibody therapies. Herbal plants, such as Indian Ayurveda, African herbal plants, and Traditional Chinese Medicines (TCM), have been studied as SARS-CoV-2 potential therapy in several countries.Objective: This review explores potential phytochemical herbals that target spike protein omicron based on the available molecular docking studies.Methods: We collected research articles on the molecular docking of phytochemicals that target spike protein omicron. Combination of several keywords: in silico OR molecular docking AND spike omicron, were used as input for Google search. Out of 83 articles from Google search, eight articles matched the inclusion criteria and were selected in this review.Result: Protodioscin from Carica papaya and Landomycin A from Aloe vera are the most potential phytochemical inhibitors against spike protein with the free binding energy of -10.77 kcal/mol and -10kcal/mol, respectively.